1979
DOI: 10.1104/pp.63.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and Ethane Production from Sulfur Dioxide-injured Plants

Abstract: After alfalfa (Medicago sativa) seedlings were exposed to approximately 0.7 microliter per liter SO2 for 8 hours, elevated ethylene and ethane production was observed. Ethylene production peaked about 6 hours and returned to control levels by about 24 hours following the fumigation, while ethane production peaked about 36 hours and was still above control levels 48 hours after the fumigation. Light had an opposite effect upon the production of the two gases: ethane production rates were higher from plants held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…This may indicate that such activity is membrane-bound. Other reports have shown that ethylene formation declines in badly stressed tissues and, at the same time, large amounts of ethane are produced (13,25). Our results support these findings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This may indicate that such activity is membrane-bound. Other reports have shown that ethylene formation declines in badly stressed tissues and, at the same time, large amounts of ethane are produced (13,25). Our results support these findings.…”
Section: Discussionsupporting
confidence: 83%
“…Release of ethane is often interpreted as indicative of (lipid) peroxidation taking place within necrotic tissues (7,12,25,26). The rates of ethane we measured from brown needles (Table I) were about one tenth to one fifth of the rates of ethylene emissions not derived from ACC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…If ethylene synthesis was stimulated in the source leaf by SO2 stress (12) or was generated by photolysis of various components in the analytical system (1), ethylene inhibition should have been more significant in the series A experiments (closed loop) than in the series B experiments. Consequently, the time course of inhibition and recovery of PA in response to SO2 exposure whould have differed from that of PB.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to SO 2 results in tissue damage and release of stress ethylene from both photosynthetic and nonphotosynthetic tissues (110,111). Fumigation with SO 2 causes a shift in cytoplasmic pH.…”
Section: Environmental Stresses Impact:-mentioning
confidence: 99%